EFEKTIFITAS PELATIHAN MEDIA AUDIO-VISUAL TERKAIT ANEMIA IBU HAMIL DALAM PENINGKATAN KOMPETENSI PETUGAS PENYULUH KESEHATAN DI KABUPATEN BANYUMAS - Masfiah, Siti; Gamelia, Elviera; Ayu Maghfiroh, Arrum Firda; Pramasatya, Adhika (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2017)
Pregnant suffers anemia can lead to infection and bleeding, which is a major factor in maternal mortality. In 2013 Central Java district recorded 3rd rank of 35 dictricts, at rate 126 per 100,000 live births. Cases of anemia in pregnant women in Banyumas accounted as 68.99%, higher than the national number. Banyumas did anemia counseling in pregnant mothers using leaflets, but did not effective. Health promotion media and materials based on local context are still limited. The ability of health workers are still based on extension activities with lectures, competency to make audio-visual health promotion is still limited. This study aimed to determine the effectiveness of audio-visual media training related anemia in pregnant women to increase the competence (knowledge and skills) of health workers in Banyumas.The study was quasy-experimental design with time series method. Population were 58 health educators in Banyumas and it was selected 33 sample by purposively. Data were collected by questionnaires for knowledge, and it was used checklist for observation the skills. For analyze the data?s normality I usedShapiro Wilk, and it used Wilcoxonto analyze the data?s difference.There was a significant difference of knowledge and skills at pretest and posttest I, but there was no significant difference on the posttest 1 and posttest II. Training of audio-visual media-related anemia in pregnant mothers increased the competence of health workers in Banyumas District.